(untitled) (Balneo and PRM Research Journal, 2024)
The study aims to perform a somatoscopic analysis on a sample of 100 prepubertal children aged 10-14 years, girls and boys, who are diagnosed with scoliosis. Somatoscopic assessment is one of the most commonly used, therefore we thought that making a way of interpreting the results could be useful to monitor postural attitude in children diagnosed with scoliosis. Identifying the early onset of physical impairment in the spine with somatoscopy can be a key factor in maintaining optimal postural status. This approach may help in achieving a way of working that limits the negative effects of scoliosis on the subjects. Materials and methods. The selection of subjects is based on exclusion and inclusion criteria related to age, comorbidities, therapeutic approach, and other criteria. Also, aspects that accompany the growth and development process of children in this prepubertal period and factors that may disturb this process are described in detail. Also in this context, we will present basic notions of body posture and etiopathogenesis of the onset of scoliotic deficiencies in children during this period of growth and development. Somatoscopic analysis is performed in the orthostatic position and is based on the identification of anatomical landmarks of the body concerning body posture. Results. From the total analyzed scoliosis, n = 100, 74% are type „C” scoliosis and only 26% are type „S” and in terms of gender, 59% are girls and 41% boys; type „C1” (Cobb angle <100) scoliosis n = 60, with an angulation < 100 are 43.24% stabilized, therefore type „C1” scoliosis are more likely to be stabilized. „S”-type scoliosis with an angulation < 150 is only 3 cases representing 11.53%, and those with an angulation from < 200 to < 400 are number 23 cases 88.64% which concludes that „S” type scoliosis is more aggressive and more difficult to manage. Conclusions. Our study show that only 13% of the subjects had a regression of the angulation following the kinetotherapy program, therefore the main objective remains to stabilize the scoliosis attitude and limit the effects of this pathology. A regular assessment and somatotopic analysis resulting in a physiotherapy exercises program containing corrective postural postures and postural education is the most beneficial approach to stabilize the postural deficit.